KEMAMPUAN OPERASI HITUNG PERKALIAN DAN PEMBAGIAN SISWA TUNAGRAHITA KELAS X SMA - Nuari, Laila Fatika; Prahmana, Rully Charitas Indra (JOURNAL OF SONGKE MATH, 2018)
The aim of this research is to know the ability of a student with mental retardation class X Senior High School in the SLB Bhakti Kencana 1 Berbah in resolving about multiplication and division operation of natural numbers. Research methods that were used the descriptive research to see student activity at the finish the same questions are given by researcher. The data was undertaken by using the video recorder to see the processing of student and test the the view student ability. The results obtained by student may be imperfect while doing the test and difficult to count multiplication and division operation. A Student could not connect the division or multiplication operation with another operation. Seen in change the repeated addition become the multiplication, a student could not be doing well. In addition a student not careful in counting and not focusing on doing the test problems.